Duopolistic Competition between Independent and Collaborative Business-to-Business Marketplaces - Kai Sülzle (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2004)
This paper studies imperfect price competition between two intermediaries in an electronic business-to-business matching market with indirect network externalities. The intermediaries differ with regard to their ownership structure: an independent third party incumbent marketplace competes with a challenging collaborative buy-side consortium marketplace in terms of attracting buying and selling firms. When firms can register exclusively with at most one intermediary, the incumbent is only able to deter entry if the number of firms taking ownership in the consortium is sufficiently small. Otherwise, the consortium can successfully enter and monopolize the market. When firms can multihome, i.e. they register simultaneously with both intermediaries, the consortium can always enter while both intermediaries stay in the market with positive profits.
Keywords: L13; L11; C78; L22; 330; B2B e-commerce; intermediation; network externalities; matching; Lieferanten-Kunden-Beziehung; E-Business; Duopol; Preiswettbewerb; Network Externalities; Intermediär